Multifunktionell allmänordbok - Tiisala, Seija (LexicoNordica, 2000)
Anmeldt værk: Lea Köykkä, Marianne Saanila, Marianne Saari, Kirsti Tirkkonen, Kari Viljanen: Suomi-ruotsi-suomi sanakirja. Jyväskylä: Gummerus 1999. 1143 s.